Comparison of Prevalence of Pre-Diabetes and Insulin Resistance among Paediatric and Adolescent Individuals with Obese Parents in Pakistan - Amin Anjum, Sarfaraz khan, Mahboob Qadir, Nasir Khan, Fouzia Ali, Muhammad Azhar Khan (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Urban familial obesity may program metabolic risk across generations, yet datacomparing paediatric and adolescent vulnerability to pre-diabetes and insulin resistance in Pakistan remain limited. This cross